Towards the New Laswell School of Public Policy - Anheier, Helmut K. (Global policy, 2019)
What model is best to drive societies forward, and with Ira Katznelson we ask: what are the best conditions for affecting the sustained contributions of schools of public policy to problem-solving?
Gesehen am 29.05.2019